An Assessment of the Effectiveness of IHL Remedies to the Civilian Population - Sidney Okwii (Uganda Christian University, 2024)
This research was done with the general objective of assessing the effectiveness of IHL remedies for the civilian population. The other objectives which were done throughout the research which include showing examples of the remedies provided, possible mechanisms, problems involved and possible solutions. In chapter two, I was able to show the legal framework governing the provision of IHL remedies to the civilian population, how the different countries apply these IHL remedies to the civilian population and the different laws that govern it in the select countries. In chapter three, I provided the right to a remedy as shown within IHL, the different principles involved with the provision of the IHL remedies. The research also showed who as a civilian is entitled to the IHL remedies, and who is liable to provide the IHL remedies to these civilians. Also within this chapter, it showed the different factors that are hindering the provision of IHL remedies to the civilians. In chapter four, I presented the summary of findings, conclusion of the research and recommendations.